Continuous monitoring of kidney transplant perfusion with near-infrared spectroscopy. Issue 10 (11th May 2018) - Malakasioti, Georgia; Marks, Stephen D; Watson, Tom; Williams, Fariba; Taylor-Allkins, Mariesa; Mamode, Nizam; Morgan, Justin; Hayes, Wesley N
ABSTRACT: Background: Current reliance on clinical, laboratory and Doppler ultrasound (DUS) parameters for monitoring kidney transplant perfusion in the immediate post-operative period in children risks late recognition of allograft hypoperfusion and vascular complications. Near-infrared spectroscopy (NIRS) is a real-time, non-invasive technique for monitoring tissue oxygenation percutaneously. NIRS monitoring of kidney transplant perfusion has not previously been validated to the gold standard of DUS. We examined whether NIRS tissue oxygenation indices can reliably assess blood flow in established paediatric kidney transplants. Methods: Paediatric kidney transplant recipients ages 1–18 years with stable allograft function were eligible. Participants underwent routine DUS assessment of kidney transplant perfusion, including resistive index (RI) and peak systolic velocity at the upper and lower poles. NIRS data [tissue oxygenation index (TOI%)] were recorded for a minimum of 2 min with NIRS sensors placed on the skin over upper and lower allograft poles. Results: Twenty-nine subjects with a median age of 13.3 (range 4.8–17.8) years and a median transplant vintage of 26.5 months participated. Thirteen (45%) were female and 20 (69%) were living donor kidney recipients. NIRS monitoring was well tolerated by all, with 96–100% valid measurements. Significant negative correlations were observed between NIRS TOI% and DUS RI at both the upper and lower poles ( r = −0.4 and −0.6, P = 0.04 and 0.001, respectively). Systolic blood pressure but not estimated glomerular filtration rate also correlated with NIRS TOI% (P = 0.01). Conclusions: NIRS indices correlate well with DUS perfusion and haemodynamic parameters in established paediatric kidney transplant recipients. Further studies are warranted to extend NIRS use for continuous real-time monitoring of early post-transplant perfusion status.